The ā-stem genitive singular in Old Prussian - Villanueva Svensson, Miguel (Vilnius University Open Series, 2022)
Root stress in the Old Prussian ā-stem gen. sg. ālg-as was taken from the homonymous o-stem gen. sg. deiw-as (Lith. lángo, Sl. *vȏrna). This analogy took place after the reshuffling of the Balto-Slavic o-stem gen. sg. *-ā as *-ās in the prehistory of Old Prussian. The shortening *-ās > -as was most probably conditioned by the fact that this ending was always unstressed.
Keywords: Old Prussian; Baltic; Slavic; declensions; genitive; accent